2014
DOI: 10.1186/1471-2164-15-1092
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of metal homeostasis by the root nodule actinobacterium Frankia

Abstract: BackgroundFrankia are actinobacteria that form a symbiotic nitrogen-fixing association with actinorhizal plants, and play a significant role in actinorhizal plant colonization of metal contaminated areas. Many Frankia strains are known to be resistant to several toxic metals and metalloids including Pb2+, Al+3, SeO2, Cu2+, AsO4, and Zn2+. With the availability of eight Frankia genome databases, comparative genomics approaches employing phylogeny, amino acid composition analysis, and synteny were used to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 147 publications
2
9
0
Order By: Relevance
“…These results are consistent with previous studies shown that the increased concentrations of heavy metals can affect the growth, morphology, and nitrogen fixation activities of soil microorganisms . Resistance of Frankia strains to some heavy metals as Cu, Zn, and Pb at certain concentrations is due to that Frankia strains have proteins for binding and sequestering of heavy metals . In general, the elevated concentrations of these elements are toxic to symbiotic Frankia strains and can affect the structural diversity of soil microorganisms as well .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with previous studies shown that the increased concentrations of heavy metals can affect the growth, morphology, and nitrogen fixation activities of soil microorganisms . Resistance of Frankia strains to some heavy metals as Cu, Zn, and Pb at certain concentrations is due to that Frankia strains have proteins for binding and sequestering of heavy metals . In general, the elevated concentrations of these elements are toxic to symbiotic Frankia strains and can affect the structural diversity of soil microorganisms as well .…”
Section: Discussionsupporting
confidence: 92%
“…It plays an important role in rehabilitation and bioremediation of contaminated soil . It has also been proved that many Frankia strains are able to accumulate and resistant to several toxic metals such as Pb, Cu, and Zn . Furthermore, ability of Frankia to bind and eliminate several toxic heavy metals has been proven .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ArsR family proteins are able to specifically bind to the metal resistance‐related operons and likely dissociate from the operons in the presence of metal ions, permitting the transcription of genes encoding proteins involved in exporting or sequestering the respective ions, a mechanism by which the bacteria can survive under metal surplus conditions . These results of genomic context analysis are consistent with the view of point previously proposed by Furnholm et al They presented that a large group of genes encoding ArsR‐like proteins are individually located in a potential operon with a gene encoding AHSA1 protein, respectively, though a direct link between ArsR and AHSA1 expression has not been elucidated. In the present study, among the 28 proteins with known structures in the AHSA1 family, there are 11 members, like CHU_1110, whose encoding genes are adjacent to and share the same promoter with a gene for ArsR family protein, respectively (Figure B), while other 16 members do not possess corresponding genomic context.…”
Section: Resultssupporting
confidence: 86%
“…Metallophores are a unique class of organic ligands released into the environment for multiple functions in metal management, such as metal acquisition and detoxification ( 12 15 ). Sequencing the genome of this strain was required to shed light upon metallophore biosynthetic genes and gene clusters that might be involved in metal homeostasis ( 16 ), metal detoxification of, e.g., copper ( 17 ), and plant- Frankia interactions ( 8 ).…”
Section: Announcementmentioning
confidence: 99%